Risks Posed by Intercrops and Weeds as Alternative Hosts to Xanthomonas campestris pv. musacearum in Banana Fields - Ocimati, Walter; Were, Evans; Groot, Jeroen C. J.; Tittonell, Pablo; Nakato, Gloria Valentine; Blomme, Guy (Frontiers in Plant Science, 2018)
Alternative host plants are important in the survival and perpetuation of several crop pathogens and have been suspected to play a role in the survival of Xanthomonas campestris pv. musacearum (Xcm) and perpetuation of Xanthomonas wilt (XW) disease of banana and enset. This study determined the potential risk posed by two weeds (Canna spp. and wild sorghum) and common banana intercrops (maize, millet, sorghum, taro and sugarcane) as alternative hosts to Xcm. The study employed screenhouse experiments, laboratory procedures and diagnosis of banana fields in XW-affected landscapes. Typical XW symptoms were only observed in artificially inoculated Canna sp., with an incidence of 96%. Leaf lesions characteristic of xanthomonads occurred on millet (50%) and sorghum (35%), though the plants recovered. No symptoms occurred in maize, sugarcane, taro or wild sorghum. However, Xcm was recovered from all these plant species, with higher recoveries in Canna sp. (47%), millet (27%), sugarcane (27%) and wild sorghum (25%). Only isolates recovered from Canna sp., millet, sorghum and wild sorghum caused disease in banana plantlets. The presence and incidence of XW on-farm was positively associated with the presence of susceptible ABB Musa genotypes and negatively with number of banana cultivars on farm and household access to training on XW management. Only 0.02% of field sampled Canna spp. plants had Xcm. Risk posed by Canna spp. on-farm could be limited to tool transmission as it has persistent floral bracts that prevent insect-mediated infections. Given the high susceptibility, perennial nature and propagation through rhizomes of Canna sp., it could pose a moderate-high risk, thus warranting some attention in the management of XW disease. Sugarcane could offer a low-moderate risk due to its perennial nature and propagation through rhizomes while risk from maize, millet and sorghum was deemed zero-low due to their annual nature, wind-mediated mode of pollination and propagation through seed. Understanding the interactions of a crop pathogen with other plants is thus important when diversifying agroecosystems. The study findings also suggest other factors such as cultivar composition and management of the disease at farm and landscape level to be important in the perpetuation of XW disease.